Pengaruh pertumbuhan ekonomi terhadap penyerapan tenaga kerja dan kemiskinan di Kabupaten Sarolangun - Sokian, Muhammad; Amir, Amri; Zamzami, Zamzami (Jurnal Paradigma Ekonomika, 2020)
This study aims to analyze the effect of economic growth on employment in Sarolangun Regency, and to analyze the effect of economic growth and employment on poverty levels, poverty depths and poverty severity levels in Sarolangun District. The data used in this empirical study are secondary data from the 2001-2017 time series originating from the Central Statistics Agency (BPS) and the Central Statistics Agency of Sarolangun Regency. The analysis method used in this research is descriptive analysis and path analysis. The results showed that economic growth had no significant effect on the dependent variable of labor. Any increase or decrease in economic growth does not affect the increase or decrease in the number of workers in the Sarolangun Regency. Economic growth has a negative direction and has a significant impact on poverty levels, poverty depth, and poverty severity through the workforce in Sarolangun District